Therapeutic Efficacy of Moxifloxacin Mucoadhesive Hydrogel for Bacterial Keratitis - Bhoi, Nipuna Kumar; Singhai, A. K.; Jain, Gaurav; Mishra, Subhendu S. (Journal of Drug Delivery and Therapeutics, 2020)
Bacterial keratitis is a hypothetically devastating corneal infection due to the opportunity of fast development; corneal devastation either to be completed in 24–48 hours with even more contagious bacterial aetiological agents. Moxifloxacin mucoadhesive Hydrogel was prepared by using polymer Hydroxy Propyl Methyl Cellulose E50 LV by hydration method. Moxifloxacin was dissolved in small quantity of water and Benzalkonium Chloride was added to the Polymer solution. The formulations were evaluated for clarity, pH measurement, spread-ability test, drug content estimation, viscosity study, in vitro diffusion study and antibacterial activity. The developed formulation exhibits the sustained release over a period of 10 hour. The optimized formulation was further evaluated with antimicrobial activity. The results of the in-vitro antimicrobial activity of hydrogel were satisfactory.Keywords: Corneal Infection, Hydrogel, Moxifloxacin, invitro release